Room Vision: Development of Mobile Application for Interior Visualization with 3D and AR Technology - Kok, Yuin Foong; Ahmad Shaubari, Ezak Fadzrin (Applied Information Technology And Computer Science, 2025)
Interior design creates functional and aesthetically pleasing living environments, and the demand for it is increasing gradually. However, people often face challenges when it comes to planning and visualizing home decoration due to the absence of visualization. Also, the existing Android interior design application often lacks an Augmented Reality (AR) feature. Therefore, this project proposed a mobile application that allows users to design and visualize their room using Three-Dimensional (3D) Manipulation and Markerless AR. Additionally, the application offers users various furniture options to design a complete room. The application is targeted at individuals who are between 18 and 30 years old and own a room. The Agile methodology is chosen for the development of the Room Vision application. The application has been developed to enable users to experiment with their designs in 3D scenes and visualize them using Markerless AR.